Carbon nanocoils-nickel foam decorated with silver nanoparticles/sheets using a novel stirring assisted electrodeposition technique for non-enzymatic glucose sensor. (February 2020) - Usman, Muhammad; Pan, Lujun; Farid, Amjad; Khan, Abdul Sammed; Yongpeng, Zhao; Khan, M. Aslam; Hashim, Muhammad
Abstract: A novel strategy has been adopted to prepare a free-standing three-dimensional (3D) electrode for nonenzymatic glucose electro-oxidation. Carbon nanocoils (CNCs) has been grown on the surface of nickel foam (NF) by catalyst assisted chemical vapors deposition to form a CNC@NF substrate. Subsequently, the 3D substrate has been coated with silver nanoparticles/sheets through electrodeposition under continuous stirring to form a network structure of Ag@CNC@NF electrode. Such a 3D catalyst electrode allows efficient diffusion and consequently boosts the electrocatalytic oxidation of glucose. Therefore, the 3D electrode provides excellent glucose sensing performance in terms of ultra-high sensitivity of 3.64 × 10 10 μA mM −1 cm −2 and quick response time of 0.1s with a detection limit of 6 nM. These features make the sensor potentially practical candidate for application to biosensors. Graphical abstract: Image 1